2006
DOI: 10.1093/jn/136.6.1466
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Protein Synthesis by Leucine Starvation Involves Distinct Mechanisms in Mouse C2C12 Myoblasts and Myotubes

Abstract: Leucine modulates protein translation in higher eukaryotes by affecting phosphorylation and the function of proteins that regulate the initiation and/or elongation steps. These include the initiation factor 4E binding protein 1 (4E-BP1), initiation factor 4E (eIF4E), initiation factor 2 (eIF2alpha), ribosomal S6 kinases (S6K1/2), and elongation factor 2 (eEF2). The alteration of protein translation by leucine starvation was studied during myogenic differentiation using the mouse C2C12 cell line as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
4
30
0
Order By: Relevance
“…It has been reported that leucine deprivation in myoblast and myotubes increased (78) and leucine administration in cell culture (44,66), rats (87,88), and humans (29,41) decreased the phosphorylation of eEF2, a key component of the elongation process. In the current study, phosphorylation of eEF2 did not differ between the CON ϩ LEU and the CON ϩ ALA groups.…”
Section: E708 Leucine Pulses Increase Lean Gain In Neonatesmentioning
confidence: 99%
“…It has been reported that leucine deprivation in myoblast and myotubes increased (78) and leucine administration in cell culture (44,66), rats (87,88), and humans (29,41) decreased the phosphorylation of eEF2, a key component of the elongation process. In the current study, phosphorylation of eEF2 did not differ between the CON ϩ LEU and the CON ϩ ALA groups.…”
Section: E708 Leucine Pulses Increase Lean Gain In Neonatesmentioning
confidence: 99%
“…Second, ingestion of small quantities of leucine rich essential amino acids activate the downstream mTORC1 target p70S6k and MPS in a comparable manner to 20–25 g of whey protein, and to a greater extent than a bolus of leucine‐deficient essential amino acids (Bukhari et al, 2015; Churchward‐Venne et al, 2012), and removal of leucine from an essential amino acid supplement following muscle loading attenuates mTORC1 signaling (Moberg et al, 2014). Finally, in C2C12 myotubes in vitro, leucine exhibits the most potent stimulation of mTORC1 signaling compared to all other amino acids (Atherton, Smith, Etheridge, Rankin, & Rennie, 2010), and its deprivation impairs protein synthesis and phosphorylation of p70S6k (Talvas, Obled, Fafournoux, & Mordier, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…In vitro cultures of skeletal muscle provide a controlled and isolated environment in which to understand cellular and molecular adaptation, and have improved our understanding of the importance of amino acids, and in particular leucine, for skeletal muscle growth (Areta, Hawley, Ye, Chan, & Coffey, 2014; Atherton, Smith et al, 2010; Talvas et al, 2006). However, a limitation of conventional in vitro methods is the inability of the rigid 2‐dimensional substrate to support muscle contraction, and as such only acute experiments are typically possible.…”
Section: Introductionmentioning
confidence: 99%
“…Leucine is an essential amino acid with a branching structure and a twin nature: it exhibits both anabolic and catabolic activities. It stimulates oxidative metabolism, especially that of 5′adenosine monophosphate-activated protein kinase (AMPK), which is the main regulator of cellular energy management (27). In the case of leucine supplementation in Ay mice, increased oxygen consumption was observed, suggesting increased energy expenditure through selective stimulation in the expression of genes important in the metabolism of fatty acids and in the biogenesis of mitochondria in the skeletal muscles (10).…”
Section: Discussionmentioning
confidence: 99%
“…It is also notable as a stimulator of muscular metabolism, boosting cellular synthesis of proteins and participating in mRNA translation. In vitro tests performed on mouse C2C12 cellular lines demonstrated that subjecting them to leucine starvation lowers protein synthesis in myoblasts (27). This amino acid also plays an important role as a repair factor.…”
Section: Discussionmentioning
confidence: 99%